Is there a method in this… madness? On variance between two manuscript copies of a Middle English Psalter - Kinga Lis (LingBaW)
The objective of the paper is to determine the extent and the possible sources of the intertextual lexical variation between two manuscript copies of a single Middle English Psalter known, among other names, as the Middle English Glossed Prose Psalter. The purpose of the paper can be understood only if one approaches the variance from a medieval perspective on text with respect for the inherent features of manuscript culture and an understanding of the exceptional character of the text analysed in the study, which topics are briefly discussed within the paper. The extent of the variance is measured in relation to the nominal choices attested in the two copies of the text, the rationale behind the variation being sought separately in each case, taking into account the contextual intricacies of all the occurrences of the nouns under analysis.